VARIABILITAS RETURN SAHAM DI SEKITAR PENGUMUMAN PERGANTIAN CHIEF EXECUTIVE OFFICER - Doddy Setiawan (Faculty of Economics and Business, Universitas Gadjah Mada, 2007)
The research aims at examining market reaction to CEO turnover announcements.The samples of the research consist of 59 CEO turnover announcements during 1992-2003periods. The author use security returns variance to examine information content of CEOturnover announcement. Friedman and Singh (1989) argue that contextual factorsmoderating the market reaction to the CEO turnover announcements. Therefore the authorconsidering two factors: the succession process and the origin of incoming CEO. The authordivide sample based on the succession process: routine and non-routine, and the origin ofincoming CEO: inside and outside firm. In the analyses process we observe market reactionto: (1) all sample of CEO turnover announcement, (2) routine CEO turnover, (3) non-routineCEO turnover, (4) inside CEO turnover, (5) outside CEO turnover, (6) routine inside CEOturnover, (7) routine outside CEO turnover, (8) non-routine inside turnover, (9) non-routineoutside turnover. The results from security return variance test shows that there areindifference variance returns to all sample, routine turnover, nonroutine turnover, insideCEO, outside CEO. When the author combines the contextual factor, he find market alsodoes not reacts to: (1) non-routine process turnover and incoming CEO come from insideand (2) routine process turnover and incoming CEO comes from outside. But, there areinformation content from: (1) routine process turnover and incoming CEO comes from insideand (2) non-routine process turnover and incoming CEO comes from outside. These resultshows that market react to smooth process succession (routine inside CEO turnover) becauseit can reduce uncertainty and incoming CEO tend to follow previous CEO strategy. Ifsuccession process is non-routine market prefer to candidate from outside because he willbring a different strategy.Keywords: CEO turnover, inside and outside CEO, routine, nonroutine